Addition of milk enhanced the total phenolic content and antioxidant activity of Camellia sinensis (Green Tea) beverages - Kee, Xiao Hui; Siti Raihanah Shafie, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study was aimed to determine the effects of adding milk, sugar and sweeteners to the total phenolic content and antioxidant activity of Camellia Sinensis (green tea) powder. Six green tea samples were brewed in cold water and whisked: Green tea powder (G), green tea powder with sugar (GS), green tea powder with aspartame (GA), green tea powder with milk (GM), green tea powder with milk and sugar (GMS) and green tea powder with milk and aspartame (GMA). The total phenolic content of green tea powder samples was evaluated by using Folin-Ciocalteu assay while α,α-diphenyl-2- picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays were used to measure the antioxidant activity. Results showed that milk addition significantly enhanced by 59.84% of total phenolic content and also increased 26.3% (DPPH) and 42.35% (FRAP) of antioxidant activity of green tea powder, as compared to green tea samples without milk (p<0.05). Strong and positive correlations were found between the total phenolic content and antioxidant activity of green tea powder by using DPPH (r=0.990) and FRAP assays (r=0.997). In conclusion, it might be beneficial when milk is added to green tea as it could help to increase its antioxidant properties.